Promoting a Community of Practice Online: How Important is Social Presence? - Carson, Maggie (Proceedings of the International Conference on Networked Learning, 2014)
Encouraging interpersonal exchanges to support collaborative learning which require an element of self-disclosure can be problematic particularly in online environment. It can take time for a diverse group of distance learners to bond with each other sufficiently to ensure meaningful relationships are formed which promote trust and give the students confidence to share their experiences. Often this time is not available. Using an innovative approach to support students, which has been used successfully face-to-face but never before online, we explore how students undertaking an online asynchronous leadership course as part of their MSc or as a stand-alone CPD module, felt supported by a ‘tool' more commonly used as an icebreaker, and often referred to as the ‘Jelly Baby Tree' (JBT). We have adapted this tool so that it can be used online to foster a sense of community. This paper attempts to answer a number of questions, including: How do students develop social presence and connect with each other on an asynchronous distance learning course? What contributes to the formation of positive relationships that promote successful interactions and encourages them to work collaboratively to enhance their learning in an online environment? Preliminary analysis suggests the students have found the JBT to be a much valued aspect of the course. They report that "the Jelly Baby Tree is the best bit of this course" giving it "the ‘human touch'", that "best of all is the Jelly Baby Tree - my stress relief and where I found so much support" while others "come away inspired every time I read someone else's jelly baby posting". Arguably, the JBT has allowed and encouraged students to be reflective and to feel able to disclose personal information about themselves and their leadership style in a safe and supportive environment. Significantly, in a diverse cultural group the JBT appears to have been perceived as a neutral, safe and non-threatening means through which students could connect with each other without misunderstanding. There has been a clear correlation between the students' interactions with the JBT, the degree of social presence and their active participation throughout the course.